Implementasi Sensor Gas untuk Mendeteksi Kesegaran Daging Menggunakan Metode Neural Network - Kiwan, Kiwan; Hidayat, Rahmat (Peneliti.net, 2024)
Quality and freshness of meat is a critical factor in the food industry to maintain consumer health. This study aims to implement a gas sensor with a Neural Network (NN) approach to detect the freshness level of meat. The NN method has proven capable of recognizing complex patterns in data, which can be applied in gas sensor analysis to obtain important information about the condition of the meat. In this experiment, 5 different gas sensors were used to measure the gases produced during meat degradation. The data from the gas sensor is then processed by the Neural Network to build a predictive model for meat freshness. Experiments were carried out using meat samples at various levels of freshness. The test results were obtained, namely the difference in readings between sensors was 2% and meat that started not being fresh occurred after 10 hours and above